(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
BACKGROUND: Modern lifestyles among people particularly in urban areas are having a risk of developing airway problems and alteration pulmonary functions due to the intensive use of air conditioners. The subjects who are frequently exposed to air conditioners showed hyper-responsiveness in respiratory tract and decreased patency of airways which resulting in decreased peak expiratory flow rate, chest expansion and increase in respiratory rate. Purpose of the study: The present study is to compare the effect of alternate nostril breathing exercise and bee breathing exercise on Peak expiratory flow rate (PEFR), chest expansion and respiratory rate in air conditioner users. METHODS: This study included 50 subjects with age of 20-50 years, those who were working in air-conditioned environment for 8-10hrs/day. Patients were selected based upon who fulfilled the inclusion criteria. The purpose of the study was explained to all subjects and the subjects were randomly assigned into either Group A (Alternate nostril breathing exercise) or Group B (Bee breathing exercise). The subjects in both groups practiced exercises of about 6 sessions/weeks for 4 weeks. The parameters assessed are Peak expiratory flow rate, chest expansion, respiratory rate was measured before and after 4 weeks of breathing exercise sessions. RESULTS: Going by the statistical analysis results, the mean improvement in PEFR (A = 34+12.91 & B = 32.8+11), chest expansion (A= 0.32+0.09 & B = 0.28+0.08) and reduction in respiratory rate (A = 3.76+1.20 & B = 3.52+0.96) of group A is very closer to group B. CONCLUSION: We conclude that both the treatments are equally effective in improving PEFR and Chest Expansion and reducing Respiratory Rate in air conditioner users.